Unlocking active metal site of Ti-MOF for boosted heterogeneous catalysis via a facile coordinative reconstruction. (22nd October 2021) - Liu, Wenxian; Que, Wenbin; Shen, Xuhai; Yin, Ruilian; Xu, Xilian; Zheng, Dong; Feng, Jinxiu; Dai, Xiaojing; Niu, Xinxin; Wu, Fangfang; Shi, Wenhui; Cao, Xiehong
Abstract: Constructing sophisticated hollow structure and exposing more metal sites in metal-organic frameworks (MOFs) can not only enhance their catalytic performance but also endow them with new functions. Herein, we present a facile coordinative reconstruction strategy to transform Ti-MOF polyhedron into nanosheet-assembled hollow structure with a large amount of exposed metal sites. Importantly, the reconstruction process relies on the esterification reaction between the organic solvent, i.e. ethanol and the carboxylic acid ligand, allowing the conversion of MOF without the addition of any other modulators and/or surfactants. Moreover, the surface and internal structure of the reconstructed MOF can be well tuned via altering the conversion time. Impressively, the reconstructed MOF exhibits ∼5.1-fold rate constant compared to the pristine one in an important desulfurization reaction for clean fuels production, i.e. the oxidation of dibenzothiophene.